Dynamics of thermoluminescence spectra of impurity-helium condensates containing stabilized nitrogen and oxygen atoms - Khmelenko, V.V.; Krushinskaya, I.N.; Boltnev, R.E.; Bykhalo, I.B.; Pelmenev, A.A.; Lee, D.M. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2012)
The results of investigations of thermoluminescence dynamics during destruction of neon–helium and krypton– helium condensates containing stabilized nitrogen and oxygen atoms are presented. Spectra of the thermoluminescence of a krypton–helium condensate contained bands of N and O atoms and NO molecules. The intensities of the bands in these spectra were found to increase simultaneously during destruction processes in the temperature range 1.5–15 K. Observation of the NO molecules provides clear evidence for chemical reactions in the nanoclusters comprising the sample at low temperatures. Destruction of neon–helium samples occurred in two stages. During the first stage the α-group of N atoms surrounded by Ne and N2 molecules dominated the spectra. During the second stage, the spectra contained intense bands of N and O atoms stabilized in a molecular nitrogen matrix. The unusual characteristics of the thermoluminescence spectra were observed, and their changes were explained in terms of the shell structure of impurity nanoclusters which comprised the impurity–helium condensates.